Design and development of web-based effective E-learning tool for computer networking subject - Wang, Weihui (2015)
Computer networking has been taught as undergraduate courses for many years. The subject of computer networking involves many concepts and technologies. To learn about the subject of networking, a top-down manner is a good approach for students, that is by starting from the application layer and working its way down toward the physical layer. Currently, in addition to attending classroom lectures, more and more students would like to accept web-based learning. Web-enhanced courses give students full control of their pace of learning; they can decide to select the topics that they don’t understand and they can view the online courses where and when they study most effectively.